The feasibility of implementing education on older person care to practice on medical units: Nurses' perceptions and the influence of practice context. (22nd August 2019) - Hunter, Kathleen F.; Dahlke, Sherry; Negrin, Kelly; Kalogirou, Maya Reshef; Fox, Mary; Antonio, Natasha; Buckborough, Neena; Morgan, Angela; Wagg, Adrian
Abstract: Aim: As part of a larger primary study on evidence‐informed practice with hospitalised older people, we aimed to (a) examine nursing staffs' perceptions of the interactive geriatric educational intervention and to explore how perceptions of their work context may influence their ability to enact the evidence‐informed assessment and care approaches discussed during the educational sessions and (b) compare differences in perceptions of context between RNs, LPNs and HCAs. Method: A survey‐based evaluation that used both closed and open‐ended questions was conducted as part of an interactive educational intervention on cognitive impairment and managing responsive behaviours. Data were gathered on participants' perceptions of the education intervention and organisational context. Results: Findings from this study suggest when education is tailored to nurses' articulated educational needs, it is well received; however, barriers to implementation exist. Assessment of the context by using a standardised survey tool to get the nursing staffs' perceptions of organisational context revealed strengths in leadership support and day‐to‐day interactions with other nurses and healthcare professionals, but potential barriers related to lack of facilitation to transfer new knowledge into practice existed. Conclusion: Providing evidence‐based education related to care of older patients and evaluating nursing staffs' perceptions of the education and their context has laid the groundwork for a long‐term relationship with the managers and nursing staff on the participating medical units. Further investigation about how best to incorporate the facilitator role into the medical units to support evidence‐based practices with older patients is warranted.  Implications for practice: While nurses are receptive to new knowledge, the unpredictable workload of acute care creates challenges to implementing this new knowledge. Assessment of contextual factors that influence evidence‐informed practice facilitates planning for implementation of new knowledge and support practice change.